À quoi sert l’organisation des sciences ? - Serge Reubi (Revue d’Histoire des Sciences Humaines)
Starting from the premise that the organisation of knowledge areas results from specific contingencies, political projects, and the convergence of particular interests, and yet has a profound impact on the knowledge constituted, I examine the supra-disciplinary category of ‘sciences humaines’ [‘humanities’]. Often overlooked, but nevertheless powerful, it is a specifically French category that arose in its present sense between the two Wars, and became hegemonic after the Second World War. It achieved this dominance not because it presented a better classificatory system than its rivals between the Wars, but because it was mobilised by a group of prominent academics and politicians, who advocated a humanist, liberal and international conception of knowledge, in a post-war institutional and political French landscape where it happened to flourish.